Social behavior and spatial orientation in rat strains with genetic predisposition to catatonia (GC) and stereotypes (PM) - V. S. Plekanchuk; O. I. Prokudina; M. A. Ryazanova (Вавиловский журнал генетики и селекции)
Various psychopathologies, including schizophrenia, bipolar disorder and major depression, are associated with abnormalities in social behavior and learning. One of the syndromes that may also take place in these disorders is catatonia. Catatonia is a psychomotor syndrome in which motor excitement, stereotypy, stuporous state, including the phenomenon of “waxy flexibility” (catalepsy), can be observed. Rats with genetic catatonia (GC) and pendulum-like movements (PM) of the anterior half of the body have physiological and behavioral changes similar to those observed in schizophrenia and depression in humans and can be considered as incomplete experimental models of these pathologies. The social behavior of the GC and PM rats has not been previously studied, and the cognitive abilities of animals of these strains are also insufficiently studied. To determine whether the GC and PM rats have changes in social behavior and spatial learning, behavioral phenotyping was performed in the residentintruder test, three-chamber test, Barnes maze test. Some deviations in social behavior, such as increased offensive aggression in PM rats in the resident-intruder test, increased or decreased social interactions depending on the environment in different tests in GC, were shown. In addition, principal component analysis revealed a negative association between catatonic freezing and the socialization index in the three-chamber test. Decreased locomotor activity of GС rats can adversely affect the performance of tasks on spatial memory. It has been shown that PM rats do not use a spatial strategy in the Barnes maze, which may indicate impairment of learning and spatial memory.